2012
DOI: 10.1093/bioinformatics/bts617
|View full text |Cite
|
Sign up to set email alerts
|

Discovering chimeric transcripts in paired-end RNA-seq data by using EricScript

Abstract: We proposed a novel computational framework, named chimEric tranScript detection algorithm (EricScript), for the identification of gene fusion products in paired-end RNA-seq data. Our simulation study on synthetic data demonstrates that EricScript enables to achieve higher sensitivity and specificity than existing methods with noticeably lower running times. We also applied our method to publicly available RNA-seq tumour datasets, and we showed its capability in rediscovering known gene fusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 28 publications
0
122
0
Order By: Relevance
“…The deep-sequencing data were mapped to human genome version hg19 and analyzed by using the software SOAPfuse (32). The human tissue RNA-seq was analyzed by EricScript (24). The identified chimeric RNAs were presented by using Circos as described (33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep-sequencing data were mapped to human genome version hg19 and analyzed by using the software SOAPfuse (32). The human tissue RNA-seq was analyzed by EricScript (24). The identified chimeric RNAs were presented by using Circos as described (33).…”
Section: Methodsmentioning
confidence: 99%
“…From paired-end RNA sequencing libraries covering 27 different tissues of 95 noncancer donors, we detected 16,026 fusion transcripts using a different software, EricScript (24), which is faster and yielded more fusion transcripts for downstream analysis. Similar to our previous findings, we found that fusion RNA profiles in each tissue or cell type were very different (Fig.…”
Section: Fusion Rna Profiling Connects Samples With Same or Similar Tmentioning
confidence: 99%
“…Repeat the procedure described above in steps 1 through 6 twice to process the same samples using FusionCatcher (Nicorici et al, 2014) and EricScript (Benelli et al, 2012). …”
Section: Basic Protocol 2: Scaling Analysis On the Cgc Platform With mentioning
confidence: 99%
“…Several computational tools have also been developed for the detection of fusion transcripts using RNA-Seq data, such as MapSplice [51], ShortFuse [52], FusionHunter [44], FusionMap [53], SnowShoes-FTD [54],defuse [55], chimerascan [56], FusionCatcher [57], TopHatFusion [44], BreakFusion [58], EricScript [59], SOAPfuse [60], FusionQ [61] , PRADA [62] and JAFFA [63]. Liu et al [64] performed a large-scale comparative study by applying these above 15 fusion transcript detection pipelines to 3 synthetic data sets and 3 real pairedend RNA-seq studies and developed a meta-caller algorithm to combine three top-performing methods (FusionCatcher, SOAPfusea and JAFFA).…”
Section: Next Generation Sequencing (Ngs): a High-performing Strategymentioning
confidence: 99%